CPR in prono possition - Emis-Vandlik, Nada A; Andjelic, Sladjana; Bogunovic, Snezana; Nikolic, Tanja (Halo 194 Scientific Journal of Emergency Medicine, 2021)
Old and new CPR guidelines assume that the patient is lying on his back, on a hard and stable surface. The prono position is usually used in the operating room and in intensive care units. COVID-19 patients are often cared for in a prono position. In the case of CA, it is necessary to start high-quality chest compressions and defibrillation.According to the current guidelines, CPR should be started in the prono position until the conditions for turning the patient on his back are met. It is recommended to perform compressions with the hands placed over the body at the level of the T7 / 10 spinal column at the usual depth and speed (5 to 6 cm, 2 compressions/sec), and self-adhesive defibrillation electrodes are placed in the antero-posterior or biaxial position. Educating health workers about the CPR in the prono position and its application in selected patients improve survival.
Keywords: cardiac arrest; cardiopulmonary resuscitation; prono possition